2009
DOI: 10.1007/s10531-009-9620-8
|View full text |Cite
|
Sign up to set email alerts
|

Area mediated shifts in bird community composition: a study on a fragmented Mediterranean grassland

Abstract: The effects of habitat fragmentation on birds have often been studied in forest specialist species. Here we aimed at comparing the response of open habitat birds within a range of habitat specialization. The study area was a Mediterranean pseudo-steppe, designated as important for conservation yet fragmented by tree encroachment. We defined bird species dependency on steppe-like habitat by a correspondence analysis, allowing us to distinguish between specialists, generalists and scrubland species. We studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
3
16
0
1
Order By: Relevance
“…1) as found for other grassland species (Davis, 2004). Similar to our results, the wheatear was found to be area-sensitive, both in rural (Caplat & Fonderflick, 2009) and urban (Jokimäki, 1999) areas. The strong influence of size that explained almost three-fourth of the variance may also be caused by the sampling of the study sites, since we selected wasteland sites with an open vegetation structure, many of them were potentially suitable for wheatears with respect to habitat features.…”
Section: Occurrence Of Wheatears -Size Of Grassland Matterssupporting
confidence: 89%
See 1 more Smart Citation
“…1) as found for other grassland species (Davis, 2004). Similar to our results, the wheatear was found to be area-sensitive, both in rural (Caplat & Fonderflick, 2009) and urban (Jokimäki, 1999) areas. The strong influence of size that explained almost three-fourth of the variance may also be caused by the sampling of the study sites, since we selected wasteland sites with an open vegetation structure, many of them were potentially suitable for wheatears with respect to habitat features.…”
Section: Occurrence Of Wheatears -Size Of Grassland Matterssupporting
confidence: 89%
“…Furthermore, the landscape scale reflects matrix suitability which is very low for the wheatear that could not be found in regular urban green spaces like parks in Berlin (Otto & Witt, 2002). Caplat and Fonderflick (2009) found a strong negative influence of a woodland matrix on the occurrence of wheatears on grassland patches, although sample size was small. For the urban setting we can state that the matrix has only a very low influence on wheatears.…”
Section: Occurrence Of Wheatears -Size Of Grassland Mattersmentioning
confidence: 85%
“…Differences in Chao-1 estimator, Brillouin's index and n were not evaluated species were even more specific, requiring the presence of large sand patches, which were provided only at the sites with sand quarrying at daily basis (Miscophus ater and Alysson spinosus). It resembles the situation within birds, where certain birds occupy the whole range of active sandpits but are mostly omitting those where the quarrying was ceased several years ago (e.g., sand martins, Riparia riparia; Heneberg 2012), while the other bird species require higher critical patch size and occupy only those post-industrial sites, which are large in size (e.g., hoopoe, Upupa epops, or northern wheatear, Oenanthe oenanthe; Caplat and Fonderflick 2009). Importantly, the rich bee and wasp sandpit communities host a wide range of associated insects, particularly from the orders Diptera, Coleoptera, and Hymenoptera, some parasitic and others commensal.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, we found that young tree plantations established on former cropland in a Mediterranean mosaic located in central Spain had (1) a detrimental effect on bird species richness in winter and (2) Previous studies on the effects of tree plantations in open habitat bird species have mostly found negative effects, particularly for the most specialized and of more conservation concern (Shochat et al 2001, Santos et al 2006, Devictor et al 2008, Caplat & Fonderflick 2009, Reino et al 2009, Butler et al 2010, Voříšek et al 2010, Fonderflick et al 2010, Méndez et al 2011. For instance, Fonderflick et al (2013) found that the abundance of openhabitat birds decreased significantly in the vicinity of edges, this negative response extended within 150 m from the edge, and the effect was disproportionately higher in open-habitat species with high conservation concern.…”
Section: Discussionmentioning
confidence: 74%
“…Cropland afforestations in southern Europe, which are mostly based on coniferous species, may cause severe damage to open habitat species, especially ground-nesting birds, many of which are of conservation concern in Europe (European Bird Census Council, 2010). These negative effect is mostly due to the replacement of high quality habitat and increasing risk of predation (Shochat et al 2001, Santos et al 2006, Caplat and Fonderflick 2009, Reino et al 2009, Voříšek et al 2010, Butler et al 2010, Fonderflick et al 2010. For instance, an assessment of nest predation rates on open farmland habitat adjacent to tree plantations in central Spain resulted in 94.2% of artificial nests that were predated three weeks after the start of the experiment (Sánchez-Oliver, Rey Benayas & Carrascal, 2014a).…”
Section: Low Effect On Open-farmland Birds Of Young Afforestations Inmentioning
confidence: 99%